2014
DOI: 10.1080/23293691.2014.966034
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Influence Hispanic College Women's HPV Vaccine Uptake Decision-Making Processes

Abstract: This qualitative study was designed to assess current and preferred social networks that influence human papillomavirus (HPV) vaccine decision making in a sample of Hispanic college women. Individual, semi-structured interviews were conducted with 41 Hispanic college women attending a large southeastern Hispanic-serving institution. Television commercials and discussions with mothers were found to be the most influential social networks for current HPV vaccination beliefs. Internet sites, close family members,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
(73 reference statements)
4
23
0
2
Order By: Relevance
“…The highest percentage (44.3%)of participants reported source of HPV vaccine information was from the mass media, with only 11.5% reported having received information about HPV vaccination from physicians. The current study results are consistent with Stephens and Thomas' study [38], where the majority of younger women heard about the vaccine via television programs and commercials. A previous study has also pointed out that exposure to television, radio, newspapers, and magazines were the main sources of HPV information among college students, followed by healthcare professionals [21].…”
Section: Discussionsupporting
confidence: 90%
“…The highest percentage (44.3%)of participants reported source of HPV vaccine information was from the mass media, with only 11.5% reported having received information about HPV vaccination from physicians. The current study results are consistent with Stephens and Thomas' study [38], where the majority of younger women heard about the vaccine via television programs and commercials. A previous study has also pointed out that exposure to television, radio, newspapers, and magazines were the main sources of HPV information among college students, followed by healthcare professionals [21].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the internet makes the mothers think about safety issues. Nevertheless, diff erent from studies such as those by McRee and colleagues (2012), Stephens and Th omas (2014), and Hughes and colleagues (2009), the mothers who participated in Ward and colleagues' (2017) study report that information found on the internet is unreliable. Th e information found on the internet, according to the mothers in the study, "signifi cantly aff ected decisions, introduced doubt, and prompted them to engage in further information-seeking" (Ward et al, 2017, p. 51).…”
Section: Using Digital Media As Information Sourcesmentioning
confidence: 81%
“…Th is shows that though opportunities for laypersons to engage with digital media are created, digital media are not necessarily their only source of information. Digital media create Article: Creating opportunities for digital engagement and participation Maja Nordtug these opportunities for engagement not only through access, but also through factors such as convenience and concerns about confi dentiality (Stephens & Th omas, 2014).…”
Section: Using Digital Media As Information Sourcesmentioning
confidence: 99%
“…Aunque poco más de la mitad pudo identificarlo como una enfermedad de transmisión sexual que se contagia por la piel, pocos saben que puede tener síntomas visibles como verrugas, que está relacionado con el CCU, de hecho un número considerable piensa que está relacionado con el SIDA o que afecta a hombres y a mujeres. Este desconocimiento o falsas creencias hacen que los jóvenes se conviertan en un grupo de alto riesgo al no tomar las medidas precisas de protección y que se alimenten falsos prejuicios (Medina et al, 2014;Stephens & Thomas, 2014). En el caso de la prevención, los jóvenes son más consientes del uso del preservativo para la prevención de enfermedades de transmisión sexual como el VPH o de la vacuna.…”
Section: Discussionunclassified